2008
DOI: 10.1111/j.1547-5069.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in Breast, Prostate, and Colorectal Cancer: Implications for Supportive Care

Abstract: Uncertainty influences patients' experiences of their cancer and their coping. Whilst it might be impossible to avoid uncertainty entirely, its negative effects might be ameliorated by understanding patients' specific needs along the disease trajectory of breast, prostate, and colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
101
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 62 publications
9
101
0
4
Order By: Relevance
“…This finding supports previous studies finding on uncertainty and unknown future in the breast cancer trajectories (Doumit et al, 2010a;Drageset et al, 2010;McCann et al, 2011). Uncertainty has been identified as one of the variables that influence the quality of life and caused psychological reactions that influence woman's experiences during cancer trajectory (Shaha et al, 2008;Tobin and Begley, 2008;Sammarco and Konecny, 2010;Drageset et al, 2011). Most women in this study were uncertain about their breast cancer symptoms and severity of their symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…This finding supports previous studies finding on uncertainty and unknown future in the breast cancer trajectories (Doumit et al, 2010a;Drageset et al, 2010;McCann et al, 2011). Uncertainty has been identified as one of the variables that influence the quality of life and caused psychological reactions that influence woman's experiences during cancer trajectory (Shaha et al, 2008;Tobin and Begley, 2008;Sammarco and Konecny, 2010;Drageset et al, 2011). Most women in this study were uncertain about their breast cancer symptoms and severity of their symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the phenomenon of uncertainty has been linked to excessive stress and difficulties with coping (Lazarus & Folkman, 1984), and has also been reported to effect adjustment and adaptation to a diagnosis of cancer and is associated with higher levels of emotional distress, poor psychosocial outcomes and reduced quality of life (Shaha, Cox, Talman & Kelly, 2008). Therefore it is suggested that infertility, or uncertainties about fertility and reproductive capability after cancer can only magnify the distress, anxiety and life disruption when superimposed on to the cancer experience (Canada & Schover, 2010;Nieman et al 2006).…”
mentioning
confidence: 99%
“…People living with cancer are faced with many demanding, illness-related experiences, including changes to everyday life, effects on quality of life and well-being, uncertainty about treatment options, treatment-related toxicity, and concerns about long-term outcomes. Uncertainty, hopelessness, dependence, role changes, and an ongoing search for meaning throughout the illness are also common experiences among individuals with cancer (Fitch, 2009;Shaha, Cox, Talman, & Kelly, 2008).…”
mentioning
confidence: 99%